PERENCANAAN TEMPAT PEMROSESAN AKHIR (TPA) SAMPAH KABUPATEN BARITO KUALA DENGAN SISITEM ANAEROBIC BIOREACTOR LANDFILL (ABL) - Fikri, Azmul Gazali (Jernih: Jurnal Tugas Akhir Mahasiswa, 2024)
The rapid population and economic growth, along with ongoing development, have both positive and negativeimpacts on society, including environmental damage due to waste. TPA Tabing Rimbah is nearing capacity, requiring expansion or a new landfill. The objective is to determine the waste weight in TPA Tabing Rimbah and plan an Anaerobic Bioreactor Landfill (ABL) system. Over a 10-year period (2022-2031), an estimated 954,677.49 m3 of waste will accumulate. The planned blocks consist of 2 landfill blocks at 12 meters height. After recirculation,block 1 has 468.17 m3/day, and block 2 has 886.99 m3/day, treated using biological methods in a leachate treatment facility(IPL). Landfill gas reaches 0.846 m3/day, which, if utilized for electricity, generates 4.016 MW power.